16O-RICH MELILITE IN CO3.0 CHONDRITES: POSSIBLE FORMATION OF COMMON, 16O-POOR MELILITE BY AQUEOUS ALTERATION - Wasson J.T.; Yurimoto H.; Russell S.S. (My University, 2001)
A problem of long-standing is the origin of the high Δ17O (= δ17O - 0.52 . δ18O) values of melilite in the refractory inclusions of carbonaceous chondrites. The spinel and, usually, also the diopside in the inclusions have ''primitive'' Δ17O =< -20%%, but in the widely studied CV3 chondrite Allende, the melilite commonly has a Δ17O of about -4+/-2%%. Recent studies of oxygen diffusion coefficients in melilite and spinel have shown that the traditional model for altering the melilite-diffusive exchange with the gas in the solar nebula-cannot occur under plausible nebular scenarios. Because of increasing evidence for aqueous alteration of Allende and other carbonaceous chondrites, we tested the hypothesis that melilite alteration might occur during aqueous alteration by studying melilite in CO chondrites showing variable degrees of alteration. Our results show that almost all melilite in CO3.2 Kainsaz and CO3.3 Ornans has Δ17O >-15%%, whereas in CO3.0 Colony (and inclusions in CO3.0 Yamato 81020 studied by Itoh et al.[2000]) Δ17O in the melilite is <-20%% (with the exception of one unusual inclusion that has undergone two melting episodes). We suggest that the O-isotopic composition of the melilite is reset by dissolution of the primitive melilite and reprecipitation in the presence of H2O having a high Δ17O value similar to that inferred from studies of CV magnetite (Choi et al., 1997, 2000). Although alteration of melilite can produce phases such as nepheline, andradite, and hedenbergite, it appears that, depending on the composition of the microenvironment, melilite present in a high-energy state (because of fine grain size, dislocations, other defects) can dissolve and reprecipitate with an O-isotopic composition intermediate between the initial composition and that of the H2O. A possible implication of our study is that the slope ~0.9 arrays observed in the minerals of refractory inclusions of many carbonaceous chondrites could be mainly the result of aqueous alteration.